Diagnosis of childhood tuberculosis in Pakistan: Are national guidelines used by private healthcare providers? - Aashifa Yaqoob; Sven Gudmund Hinderaker; Razia Fatima; Hemant D. Shewade; Nadia Nisar; Ahmed Wali (International Journal of Infectious Diseases, 2021)
Background: The National Tuberculosis Control Program (NTP) in Pakistan developed, with the Pakistan Paediatric Association, a pediatric scoring chart to aid diagnosis of childhood tuberculosis (TB). Our study compared the diagnostic practice of private healthcare providers in Pakistan with the NTP guidelines. Methods: A cross-sectional study comparing diagnosis of TB in children <15 years by Non-NTP private providers with the NTP’s pediatric scoring chart. A generalized linear model was used to determine the difference in adherence by Non-NTP private providers to the NTP guidelines for childhood TB diagnosis by associated factors. Results: A total of 5193 (79.7% of presumptive childhood TB cases identified in the selected districts during the study) children were diagnosed with TB by Non-NTP private providers. A strong clinical suspicion of TB was present in 17.3%, and chest x-ray was suggestive of TB in 34.3%. The Kappa score between Non-NTP private providers and the NTP guidelines for diagnosing TB was 0.152. Only 47.8% of cases were diagnosed in line with the NTP guidelines. Children <5 years old with a history of TB contact had a higher chance of being diagnosed according to the NTP guidelines. Conclusion: This study indicates a low adherence of NTP guidelines for diagnosing childhood TB by private providers in Pakistan.